Od zbrodni przez media do wyroku - Gruza, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Every day we read about accidents, crimes, and felonies. Therefore, it is worthwhile thinking like media dazzled with the felony and cruelty, we are changing ourselves, as the narrative in the mass media can influence our mental health and sense of security. It is worthwhile looking at these problems not only from the perspective of the observer and the reader of media news reports , but also the unjustly sentenced, experiencing the effects of the media narrative.
Keywords: przestępstwo; media; zdrowie psychiczne; bezpieczeństwo